The current trend for prosthetic joint infection diagnosis from culture to molecular: a literature review - Augustine Natasha; Mardiastuti Wahid; Pratiwi Sudarmono (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2021)
Pathogen identification in prosthetic joint infection is necessary to achieve optimal patient management. The specimens for diagnosis of prosthetic joint infection could be the synovial fluid, the tissue obtained intraoperatively, and the biofilm from the implanted prosthesis. Because of the low sensitivity of the conventional specimen culture method, the preanalytic treatment of the specimen was widely studied to increase the yield of detection. This review aimed to describe the current specimen processing methods used in the clinical setting to increase the pathogen detection rate. A blood culture bottle, tissue homogenization, and explanted prosthesis sonication were the most studied methods with a good result. Molecular methods were also developed to reduce the time of pathogen detection. MALDI-TOF was studied to reduce identification time after a positive culture. Other molecular methods such as polymerase chain reaction and next-generation sequencing were studied to omit the culture step and reduce detection time. However, the impracticality and the inconsistent sensitivity of certain specimens from the molecular methods limit its application in the clinical setting. Specimen culture remains as a crucial step in the current prosthetic joint infection, with the improvement of the molecular methods toward a better prosthetic joint infection diagnosis.